2016
DOI: 10.4103/0974-7796.184898
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renal vascular anatomy in live renal donors: Role of multi detector computed tomography

Abstract: Background:Evaluation of renal vascular variations is important in renal donors to avoid vascular complications during surgery. Venous variations, mainly resulting from the errors of the embryological development, are frequently observed.Aim:This retrospective cross-sectional study aimed to investigate the renal vascular variants with multidetector computed tomography (MDCT) angiography to provide valuable information for surgery and its correlations with surgical findings.Materials and Methods:A total of 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The incidence of supernumerary renal veins varies but is frequently seen more on the right side. 31 Our study revealed 16.1% of donors on the right side and 3.8% on the left side. During nephrectomy, the vein is sacrificed when venous drainage of the smaller vein is <20%.…”
Section: Discussionmentioning
confidence: 52%
“…The incidence of supernumerary renal veins varies but is frequently seen more on the right side. 31 Our study revealed 16.1% of donors on the right side and 3.8% on the left side. During nephrectomy, the vein is sacrificed when venous drainage of the smaller vein is <20%.…”
Section: Discussionmentioning
confidence: 52%
“…Renal vascular anomalies are rare, but if unexpected may represent an important concern in candidates for living kidney donation given its potential for donor and organ damage (vascular injury) in unexperienced hands. Hence, preoperative assessment of pertinent vascular anatomy by means of high resolution cross-sectional imaging is crucial to avoid potential complications, resulting advisable in every potential candidate to better select the most appropriate operation strategy [13].…”
Section: Discussionmentioning
confidence: 99%
“…easily detected on computed tomography scans, so that fatal threats during major surgeries such as donor nephrectomies in otherwise healthy donors to be avoided [11].…”
Section: Discussionmentioning
confidence: 99%